Nanopore electric snapshots of an RNA tertiary folding pathway - Xinyue Zhang; Dong Zhang; Chenhan Zhao; Kai Tian; Ruicheng Shi; Xiao Du; Andrew J. Burcke; Jing Wang; Shi-Jie Chen; Li-Qun Gu (Nature Communications, 2017)
While RNA folding is critical for its function, study of this process is challenging. Here, the authors combine nanopore single-molecule manipulation with theoretical analysis to follow the folding of an RNA pseudoknot, monitoring the intermediate states and the kinetics of their interconversion.